TEOLOGI TANAH: KONFLIK AGRARIA DALAM PERSPEKTIF HADITS - Faridatunnisa, Nor (IAIN Palangka Raya, 2022)
Oil occupies an important position for humans. For this reason, disputes often arise in the community because of fighting over land ownership rights, or agrarian conflicts. This reality demands a study of how Islam speaks related to land ownership. This research is a library research using content analysis method, where data related to land ownership in Islamic theology, especially from the traditions of the Prophet will be presented for being analised after that. The results showed that based on the general understanding of soil theology initiated by the scholars, it can be concluded that in soil theology there are two main elements, namely faith and charity. In the context of faith, the Prophet had stated that basically all land on earth is the prerogative of Allah. Faith will encourage oneself to be humble and aware that humans are only creatures. This awareness, will avoid greed in controlling the land. Furthermore, the basis of faith that has been owned will lead to a noble attitude of charity as taught by the Prophet. In addition, the Prophet has also taught how to treat land well, namely by using it according to the needs for land that can be owned personally and maintaining its sustainability for conservation land which is owned by the state.ABSTRAKTanah menduduki posisi penting bagi manusia. Karena itulah, seringkali muncul persengketaan di masyarakat karena berebut hak milik atas tanah, atau konflik agraria. Realitas ini menuntut adanya kajian bagaimana Islam berujar terkait dengan kepemilikan tanah. Penelitian ini merupakan penelitian kepustakaan dengan metode content analysis, dimana data terkait kepemilikan tanah dalam Teologi Islam, khususnya dari hadis-hadis Nabi akan dipaparkan untuk kemudian dianalisis. Hasil penelitian menunjukkan bahwa berdasarkan pemahaman umum atas teologi tanah yang digagas oleh para ulama, dapat disimpulkan bahwasanya dalam teologi tanah terdapat dua unsur utama, yakni iman dan amal. Dalam konteks iman, Nabi sudah jauh-jauh hari menyatakan bahwa secara mendasar semua tanah di muka bumi adalah hak prerogatif Allah. Iman akan mendorong diri bersikap tawadhu